A marginal resource for civic identity - Olsson, Tobias (Javnost (Ljubljana), 2006)
Within research as well as policy debates, much effort has been put into analysing the Internet's significance for democracy. These discussions have certainly contributed to progress in the area by, for instance, statistically pointing out the differentiated access to the new ICT among various social groups and - mainly theoretically - suggesting in what ways the Internet can become a tool for democracy. However, these analyses also hold a few blind spots, of which this article discusses two. Firstly, they have paid only minimal attention to the everyday users' experience of new ICT. Secondly, they have usually focused quite exclusively on the Internet rather than looking at it as part of an already-established media environment. This article is an initial effort to compensate for these shortcomings. It departs from the concept 'civic identity' and analyses qualitative data on Swedish working class users' use and perception of the Internet as well as 'traditional media.' For those who believe the Internet to be an inclusive medium and as such a tool for democracy, the article's empirical results are somewhat discouraging. For instance, the empirical and analytical discussions reveal that the traditional media - TV, newspapers and radio - are far more important than the Internet to the working class users' civic identities.
Keywords: Švedska; družbene skupine; delavci; identiteta; država; state; democracy; demokracija; mass media; množični mediji; informacijska tehnologija; information technology; komunikacijska tehnologija; internet; dostopnost